Tierra y libertad : land, liberty, and Latino housing - Bender, Steven (New York : New York University Press, 2016)
'Tierra y Libertad' surveys the terrain, culture, and history of Latino/as and housing. Employing a vital historical perspective, it traces its core theme of how Latino/as once held expansive ranchland in the Southwest but are now primarily a landless population spread throughout the U.S. that clings to marginal property rights and precarious ownership through overcrowded urban rental units, transitory rural living arrangements, and, at best, home acquisitions financed by high-risk subprime mortgages.
Previously issued in print: 2010.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on April 12, 2016).
Keywords: Hispanic Americans -- Housing; American Dream; Immigrants -- United States; Society; United States of America, USA; South & Central America, Latin America; Ethnic studies; Legal history; Property law: general